Optimal Design of Surface-Permanent-Magnet-Type BLDC Motor for Radiator Fan to Reduce Cogging Torque using Genetic Algorithm - Baek, Soo-Whang (International Journal of Engineering and Technology, 2018)
Background/Objectives: This paper proposes an optimal design method to reduce the cogging torque of a surface permanent magnet (SPM)-type BLDC motor widely used for automotive radiator fan by changing the shape of permanent magnet attached to rotor.Methods/Statistical analysis: To reduce the cogging torque, we designed the shape of the permanent magnet and used a genetic algorithm (GA), which is a type of optimization method. Three design variables, i.e., the width of the permanent magnet, radius of the outer diameter, and thickness of the permanent magnet, were set when the optimization method was applied.Findings: In recent years, there has been an increasing demand for a vehicle electric system that uses a motor to improve the fuel efficiency and output of a vehicle. Among them, the development of a BLDC motor using a DC power source is actively being carried out. BLDC motors use permanent magnets in the rotor to enable miniaturization for vehicle mounting. However, a BLDC motor having a permanent magnet structure necessarily generates a cogging torque owing to a difference in reluctance, which causes noise and vibration. The cogging torque varies depending on the shape of the permanent magnet and core of the rotor, and it can be reduced by changing the magnetâ€™s shape. Using the proposed optimal design algorithm, BLDC motors for four pole and 24 slot radiator fans with rated 100W were designed. To verify the design results, the cogging torque and torque ripple characteristics were calculated by finite element analysis. As a result of the finite element analysis, the cogging torque and torque ripple of the optimal model have been reduced compared to the initial model. Finally, it has been confirmed that it is appropriate to reduce the cogging torque characteristics of a BLDC motor for a radiator fan by implementing the proposed optimal design algorithm.Improvements/Applications: The proposed optimal design procedure is suitable for improving the performance of the SPM type BLDC motor that drives the automotive radiator fan, as it reduces the motorâ€™s cogging torque. The proposed optimal design procedure is able to stabilize the operation of the vehicle radiator fan by reducing the cogging torque and torque ripple of the BLDC motor.Â Â